Revisiting the starting age of colorectal cancer screening in Hong Kong: a cost-effectiveness analysis - Junjie Huang; Claire Chenwen Zhong; Victor Chan; Xianjing Liu; Chaoying Zhong; Jianli Lin; Junjie Hang; Jinqiu Yuan; Wanghong Xu; Mellissa Withers; Andrew T. Chan; Martin C.S. Wong (The Lancet Regional Health. Western Pacific)
Background: The incidence of early-onset colorectal cancer (CRC) is rising in Hong Kong. While the existing CRC screening program has been effective, it does not prioritize the prevention of early-onset cases in individuals under 50. This study aims to evaluate the cost-effectiveness of various starting ages for colorectal cancer screening in an Asian population. Methods: In this simulation study, we analyzed 100,000 individuals in Hong Kong, initiating screening at ages 40, 45, and 50, and continuing until age 75. Two primary screening techniques were employed: colonoscopy and the fecal immunochemical test (FIT). The effectiveness of different strategies was assessed based on life-years gained, and cost-effectiveness was measured using the incremental cost-effectiveness ratio (ICER). Findings: The ICERs for initiating FIT screening at ages 50, 45, and 40 were USD 53,262, USD 67,892, and USD 86,554, respectively. For colonoscopy, the ICERs were USD 267,669, USD 312,848, and USD 372,090 for the same starting ages. Overall, the FIT strategy proved to be more cost-effective. At compliance rates of 70%, 80%, and 90%, FIT screening at age 45 yielded 2,135, 2,296, and 2,438 life-years gained, respectively, while colonoscopy at age 45 yielded 2,725, 2,798, and 2,855 life-years. With increased compliance, FIT could achieve a similar number of life-years as colonoscopy at a lower cost. Interpretation: In Hong Kong, initiating CRC screening with FIT at age 45 is a cost-effective strategy, offering a balance of cost savings and lives saved compared to screening at age 50. This study supports the feasibility and economic viability of implementing FIT as the primary CRC screening method in Hong Kong. Funding: The study was funded by Health and Medical Research Fund (HMRF, Ref. No. 20210711), Health Bureau, Hong Kong SAR. This work was delivered as part of the PROSPECT team supported by the Cancer Grand Challenges partnership funded by Cancer Research UK, the National Cancer Institute (OT2CA297680), the Bowelbabe Fund for Cancer Research UK and Institut National Du Cancer. Dr. Chan is an American Cancer Society Research Professor.